2017
DOI: 10.3389/fmicb.2017.02451
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Microbial Communities and Quantitative Chemodiversity in Layers of Marine Sediment Cores from a Causeway (Kaichu-Doro) in Okinawa Island, Japan

Abstract: Microbial community diversity and chemodiversity were investigated in marine sediments adjacent to the Okinawan “Kaichu-Doro” Causeway, which was constructed 46 years ago to connect a group of four islands (Henza-jima, Miyagi-jima, Ikei-jima, Hamahiga-jima) to the Okinawan main island. This causeway was not built on pilings, but by land reclamation; hence, it now acts as a long, thin peninsula. The construction of this causeway was previously shown to have influenced the surrounding marine ecosystem, causing e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The considerably more OTUs were observed in marine sediments. Totals of 6039 OTUs, 6059 OTUs, and 5700 to 7600 OTUs were obtained from marine sediments around the Kaichu-Doro Causeway in Okinawa, Japan [31], marine sediments in Yam O Wan Bay, Hong Kong [32], and marine sediments from Jeju Island, South Korea [20], respectively. Moreover, this study found that the proportions of the Proteobacteria were highest in all sampling sites, followed by the Bacteroidetes and Actinobacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The considerably more OTUs were observed in marine sediments. Totals of 6039 OTUs, 6059 OTUs, and 5700 to 7600 OTUs were obtained from marine sediments around the Kaichu-Doro Causeway in Okinawa, Japan [31], marine sediments in Yam O Wan Bay, Hong Kong [32], and marine sediments from Jeju Island, South Korea [20], respectively. Moreover, this study found that the proportions of the Proteobacteria were highest in all sampling sites, followed by the Bacteroidetes and Actinobacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The microbial community structures of sediment samples from different environments exhibit various characteristics. Microbial community examination of sediments from different regions-including the Sea of Japan, the South China Sea, the Sea of Okhotsk, the Marginal Sea of Peru, the Red Sea, the Bohai Sea, and Okinawa-has shown that the structure and diversity of their microbial communities are divergent [17,[22][23][24][25][26][27]. For example, in some polluted areas, the petroleum-eating bacteria-which belong to the phyla Pseudomonadota, Bacillota, Actinomycetota, and Bacteroidota-are abundant in coastal sediments [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, spatial surveys of marine biodiversity have primarily focused on megafauna and macrofauna (Gaston, 2000; Tittensor et al, 2010) or microfauna (Sunagawa et al, 2015; Soliman et al, 2017), rather than meiofauna (the polyphyletic group of organisms that fall somewhere in between) (Lambshead & Boucher, 2003; Giere, 2008; Fonseca et al, 2010; Curini-Galletti et al, 2012; Fonseca et al, 2014; Guardiola et al, 2015; Leray & Knowlton, 2015; Guardiola et al, 2016). These organisms arguably represent the most abundant component amongst benthic metazoans in all marine systems from the intertidal zone to the deep-sea floor (Danovaro & Fraschetti, 2002; Giere, 2008).…”
Section: Introductionmentioning
confidence: 99%